Coping strategies and the influence of perceived parental support in junior national age swimmers - Lafferty, M. E.; Dorrell, K. (Journal of Sports Sciences, 2006)
This study examines how national junior age group swimmers cope with poor performance and explores whether coping strategy use changes with perceptions of parental support. One hundred and four junior age group swimmers (mean age 14.2 years) completed a modified version of the COPE scale (Crocker & Issack, 1997) and the perceptions of Perceived Parental Support Scale (Van Yperen, 1995). Results showed that the swimmers in this sample used a mixture of behavioural and cognitive strategies with an emphasis upon individual or internally focused approaches. When analysing coping strategies and perceptions of parental support (high, medium and low), significant differences were found in the use of behavioural and cognitively orientated approaches. When perception of parental support was low, swimmers reported using less active and training-orientated mechanisms and a tendency to use strategies such as self-blame and venting of emotion. These findings suggest that the effectiveness and ability of coping strategies to adapt to differing situations may be contingent upon perceptions of perceived support for junior swimmers. This highlights an area for future research.